Digital Rights and Early Childhood Education: A Legal Perspective - KOL, Suat; Şenöz, Eslem Gözde (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
Digital rights refer to the freedoms and protections individuals, including children, are entitled to in the digital environment. In an era of rapid digitalisation, ensuring these rights, especially within early childhood education, has become increasingly significant. Children are active participants in the digital world, and their rights to safely access, use, and interact with digital content must be viewed from educational and legal perspectives. Core concerns include safeguarding children’s presence in digital spaces, protecting their data, and ensuring equitable access to appropriate digital resources. In this regard, Digital Rights Management (DRM) systems play a vital role in regulating access and ensuring content protection, while emerging technologies such as blockchain enhance transparency and security in copyright enforcement. Access to digital content is central to children's learning and development, making it a public responsibility to protect these rights through sound policy and regulation. At the same time, digital engagement brings potential risks, such as digital addiction, which can adversely impact children’s cognitive, emotional, and social development. Research indicates that familial, environmental, and educational factors often influence this addiction. Thus, parents and educators play a critical role in creating a safe and balanced digital experience for children. Their awareness, supervision, and attitude towards digital tools shape how children navigate online platforms. Therefore, stakeholders—governments, educators, and families alike—must collaborate in creating frameworks that uphold children's digital rights and promote responsible digital citizenship from an early age.